The Association Of Neutrophil Lymphocyte Ratio And In-Hospital Mortality In Acute Coronary Syndrome Patients: Meta Analysis - Nurul Fajri Widyasari; Helda Helda; Rizki Febriawan (Green Publisher Indonesia, 2022)
Coronary artery disease, including acute coronary syndrome (ACS), is a major cause of mortality and morbidity worldwide. The neutrophil lymphocyte ratio (NLR) is a nonspecific marker of inflammation and previous studies have shown that increased NLR is associated with mortality in acute coronary syndrome patients and may act as a prognostic marker. The aim of this study was to assess the association of NLR and in-hospital mortality in ACS patients. The method used in this study was, Literature search was carried out using the Ebsco, Embasse, Nature, Proquest, PubMed, Science Direct and Scopus databases until March 2022 to find an observational cohort study that assessed the association of NLR and in-hospital mortality in ACS patients. A systematic review of published studies following the preferred reporting items for systematic review and guideline meta-analysis (PRISMA) was conducted. Study quality was assessed with the Newcastle Ottawa Scale (NOS) and only high quality studies were included in this meta-analysis. The primary outcome was in-hospital mortality and the effect was measured in Risk Ratio (RR) and 95% CI. Conclusion: A high NLR increases the risk of in-hospital death in acute coronary syndrome patients. Further studies in large settings are needed to assess the NLR threshold values ​​that can predict in-hospital mortality in acute coronary syndrome patients